Tarkhan : A Nomad Institution in an Islamic Context - Marie Favereau (Université de Provence, 2018)
Abstract: Under the Chinggisids, Tarkhan was not a purely honorary title but referred to a personal status. This article examines the development of the Tarkhan status in late-fourteenth-century Golden Horde. Its point of departure is an immunity-yarlïq granted by Khan Temür-Qutluq (r.1391-1399) to a wealthy Muslim landowner that combines an ownership contract with a list of personal tax exemptions. This contribution traces back the landowner’s family to its Crimean estates and clarifies the role the family played as local supporters of the Jochids. The study of this family and its possessions offers important insights into the socio-economic organisation of the Golden Horde and shows how the khans convinced local elites to support them. Even if Tarkhans did not fulfil any office and were not part of the ruling inner circle, they played an essential role in local life and were key agents in the spread of Islam.